Mechanical properties of concrete containing coconut shell as coarse aggregate replacement / Muhamad Azffar Irham Mat Zain ... [et al.] - Mat Zain, Muhamad Azffar Irham; Zuhan, Nurizaty; Sa’ari, Nadiah; A. Mujedu, Kasali; Kado, Bishir (2024)
The increase in the price of traditional construction materials is a serious issue. Concrete, which is made of cement, sand, coarse aggregate, and water, is widely used as a building material. However, an increase in concrete production has certain negative consequences for the environment, such as the extraction of natural resources such as aggregate. Therefore, innovation in concrete materials without neglecting strength can always be done. Coconut shells are one of the recycled materials that can be used as a replacement for conventional construction materials such as aggregate. The aim of this research is to investigate the properties of concrete by using coconut shell as a partial replacement for coarse aggregate. A total of 60 samples with 0%, 10%, 20% and 30% of coconut shells as coarse aggregate for concrete replacement were cast. The properties of fresh and hardened concrete with coconut shell as coarse aggregate replacement were determined at 7, 14, and 28 days of curing ages. The results showed that concrete with coconut shell as a coarse aggregate replacement had a positive impact on workability, porosity, density, and UPV but not on compressive and tensile strength. However, the concrete made from coconut shell aggregates satisfied the minimum requirements of normal concrete, resulting in the acceptable strength required for M30 grade concrete. It can be used as lightweight concrete. Using coconut shell as a replacement for aggregate is not only cost-effective and environmentally friendly, but it also helps solve the problem of conventional material shortages, such as coarse aggregate. It can also help to solve the problem of waste disposal.